Irisin Has Evident Association With Insulin, HOMA-IR, and Glucagon In Obese Diabetic and Non-Diabetic Iraqi Women - Athir Kadhim Mohammed; Faris Abdul Kareem Khazaal; Sama Hazim Mohammed Salih (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Objective: We aimed to explore that the association of irisin with various anthropometric and metabolic parameters in obese diabetics and non-diabetics Iraqi women. Methods: Eighty obese Iraqi women participated in this cross-sectional study grouped into 40 obese and 40 obese diabetics. The correlation coefficient between circulating irisin levels and metabolic parameters were performed. Results: Serum irisin levels in obese group showed highly significant positive correlations with body weight, WC, BMI, FPG, fasting insulin (FI), HOMA-IR and glucagon (r=0.8684, P> 0.0001 ; r = 0.8104, P> 0.0001; r = 0.8285, P <0.0001; r = 0.5876, P> 0.0001‎; r = 0.5283, P> 0.0005‎; r = 0.0005, P <0.0001; r = 0.5244, P> 0.0005) respectively,  and significant negative correlation ‎with FPG, FI and HOMA-IR (r=-0.3246, P<0.041; r=-0.7903, P<0.0001; r=-0.6105, P<0.0001) respectively. Stepwise regression results showed that body weight, FPG, HOMA-IR and glucagon had significant independently related with irisin (β=‏2.3150, P<0.0001; β=-‎1.2200, P=‎0.0002; β=‎21.8760, P=0.02‎; β=‎-20.9800, P<‎0.005; β=‎0.0468, P=0.037) respectively. Conclusions: Irisin had a strong positive correlation with anthropometric parameters. Irisin independently associated with body weight, glucagon, HOMA-IR and FPG